Evaluation of Nutrition Intervention On Snack's Eating Habits and Anthropometric Status of College Students in Malang City - Rany Adelina; Carissa Cerdasari; Rani Nurmayanti; Elok Widayanti (Amerta Nutrition, 2021)
Background: Problems that arise in students based on the results of the 2016 study indicate that more than 80% of students like to eat unhealthy snacks such as packaging snacks, fried foods, instant noodles, and meatballs. Where snacks contain high energy, carbohydrates, protein, saturated fat, and salt. The excess energy and nutrients intake are related to increasing the metabolic incidence of syndromes and the main risk factors for cardiovascular disease.Objectives: This study aims to determine the effectiveness of giving nutritional interventions to eating habits and anthropometric status of college students in Malang.Methods: The quasi-experimental design with 31 participants from college students in Malang. Nutrition interventions provided in the form of education related to healthy snacks and assistance in making healthy snacks. The instruments used were pretest-posttest, questionnaire, and semi FFQ. Data processing was carried out by descriptive statistical analysis and dependent t-test at a 95% confidence level.Results: There was a significant increase in knowledge related to healthy snacks for subyek penelitiants (p <0.01) indicated by the results of the pre-test and post-test. There was an increase in the influence with nutrition claims by 31% and there was a significant difference between before and after the intervention (p = 0.013). The results of a healthy semi FFQ snack for the fruit category experienced a significant increase after being given an intervention program (p <0.01), while the semi FFQ results for unhealthy snacks for the category of salted crackers, chocolate/candy, pudding, and market snacks tended to decrease in consumption although not significant. The prevalence of overweight and obese in participants before being given intervention was 29% and decreased after being given intervention to 22.6% even though there was no significant difference (p = 0.096).Conclusions: There is an increase in the influence of 'nutrition claims' and fruit consumption significantly. While the prevalence of obese tends to fall even though it is not significant between college students.